2007
DOI: 10.3201/eid1305.060572
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Pathogenesis of Avian Influenza A (H5N1) Virus in Humans

Abstract: Apoptosis may play a crucial role in the pathogenesis of pneumonia and lymphopenia caused by this virus in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
159
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(171 citation statements)
references
References 20 publications
11
159
0
1
Order By: Relevance
“…ROS formation may result in caspase-dependent apoptosis and virus-induced apoptosis may be a major mechanism in the destruction of epithelial cells infected with H5N1 both in vitro and in vivo [8,25]. To investigate the influence of NAC on H5N1-induced apoptosis in A549 cells, cells were treated with or without NAC and infected with H5N1 at an MOI of 0.01.…”
Section: Influence Of Nac On H5n1-induced Caspase Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS formation may result in caspase-dependent apoptosis and virus-induced apoptosis may be a major mechanism in the destruction of epithelial cells infected with H5N1 both in vitro and in vivo [8,25]. To investigate the influence of NAC on H5N1-induced apoptosis in A549 cells, cells were treated with or without NAC and infected with H5N1 at an MOI of 0.01.…”
Section: Influence Of Nac On H5n1-induced Caspase Activationmentioning
confidence: 99%
“…Human infections with highly pathogenic influenza A H5N1 viruses are associated with severe pneumonia, lymphopenia, high viral loads in the respiratory tract, and hyper-induction of cytokines and chemokines (cytokine storm) [7]. Pathological investigations revealed that induction of apoptosis may be a major mechanism in the destruction of alveolar epithelial cells in humans infected with H5N1 [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, these molecules can also cause the host harm by a phenomenon known as cytokine storm. Cytokine storm has been convincingly documented both in experimental animals infected with the 1918/1919 and H5N1 influenza viruses (2,(10)(11)(12)(13) as well as in humans (14)(15)(16)(17)(18) succumbing to H5N1 infection. Although antiviral drugs can be used to treat the virus, a strategy to balance the resultant cytokine release and lung injury while maintaining benefits of the antiviral protective immune response is needed (19).…”
mentioning
confidence: 99%
“…While lymphopenia, hypercytokinemia, and hemophagocytosis have been the most notable clinicopathological findings, the biological basis accounting for the severity of H5N1 infection in humans remains unknown (10,51). In a recent study, apoptosis among the alveolar epithelial cells of two patients who died of H5N1 infection was observed (53), suggesting that apoptosis may play a role in H5N1 pathogenesis in humans.…”
mentioning
confidence: 99%